WATER POLLUTION INDEX: MEASUREMENT OF SHALLOW WELL WATER QUALITY IN URBAN AREAS - Ronny, Ronny; Arif, Muhammad Ikbal; Notobroto, Hari Basuki (International Journal of Environment, Engineering and Education, 2019)
Determination of water quality status based on the pollution index method. Water said to polluted if it cannot use according to its standard designation. The purpose of this research is to identify and find out the level of pollution contained in shallow well water used by communities in urban areas. Water quality index measurements using the Storet Method. This study uses ten samples with techniques Purposive random sampling with well water sources used by people in Makassar, especially in Untia Sub-District, Makassar, South Sulawesi. The number of samples used was 15 water samples taken each week with a total of 10 shallow well water sample points. The parameters measured in the study are Iron (Fe), Manganese (Mn), Total Coliforms, Total Dissolved Solids (TDS). The results of the study showed that the condition of shallow well water quality classified in category D, which heavily polluted which means it not recommended to use before filtering. The increase in parameters that have exceeded the maximum quality standard comes from natural sources and high domestic waste from community activities. Water pollution is a condition in which a water reservoir changes due to human activity ? the change caused by the entry of substances that should not be in the water.